Applications of ultrasound in refining vegetable oil - Yıldız, Gökçen (Nova Science Publishers, Inc., 2023)
Ultrasound applied in the refining stages provides most of the activation energy required for the reaction to occur due to the cavitation force. In the light of the theoretical and practical information obtained in the studies, ultrasound application has been evaluated as an innovative technique due to the shortening of the processing time, low energy consumption, reducing the use of chemicals, and minimal effect on the bioactive components in the oil's structure. Therefore, it can be concluded that ultrasound application can provide significant advantages in the removal of sticky substances from the vegetable oil refining stages and in the deacidification stages as well as in the bleaching stages. As a result, it is thought that it is necessary to accelerate new scientific studies on the use of ultrasound applications in vegetable oil refining stages. In this review, the principles of ultrasound application, ultrasound application methods, removal of sticky substances in the refining of vegetable oils, ultrasound applications in degumming, deacidification and bleaching stages, and scientific studies on this subject were examined in detail. © 2023 Nova Science Publishers, Inc. All rights reserved.
Keywords: Bleaching; Deacidification; Degumming; Ultrasound; Vegetable oils